2014
DOI: 10.1210/jc.2014-1384
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphisms in the Associations of BMI and Body Fat with Indices of Pubertal Development in Girls and Boys

Abstract: Significant sexual dimorphisms in the manifestations of pubertal development are seen in obese girls and boys. Two known effects of obesity, increased peripheral conversion of low-potency androgens to estrogens by adipose tissue-aromatase and increased insulin resistance, may be in large part responsible for these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 82 publications
8
63
3
4
Order By: Relevance
“…Crocker et al reported a negative association between BMI z score and TV. 10 Average TV was 7.5 mL (95% CI 6.9-8.1) for obese (n = 208) boys (mean age 11.7 years) compared with 9.2 mL (95% CI 8.6-9.8) for nonobese boys (mean age 11.2 years; n = 231), but this study did not perform comparisons of only overweight children. In a longitudinal cohort of mostly Caucasian boys from the National Institute of Child Health and Human Development Study of Early Childcare, Lee et al found that boys with the highest trajectory of BMI z score had the lowest attainment of Tanner stage 2 puberty by age 9 years, but this study did not compare children based on weight classification.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Crocker et al reported a negative association between BMI z score and TV. 10 Average TV was 7.5 mL (95% CI 6.9-8.1) for obese (n = 208) boys (mean age 11.7 years) compared with 9.2 mL (95% CI 8.6-9.8) for nonobese boys (mean age 11.2 years; n = 231), but this study did not perform comparisons of only overweight children. In a longitudinal cohort of mostly Caucasian boys from the National Institute of Child Health and Human Development Study of Early Childcare, Lee et al found that boys with the highest trajectory of BMI z score had the lowest attainment of Tanner stage 2 puberty by age 9 years, but this study did not compare children based on weight classification.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, other studies have reported later attainment of puberty with excess weight. [8][9][10] Existing studies on the relationship between weight and pubertal attainment in boys have been limited by small sample sizes, 6,11,12 differing definitions of puberty (eg, using proxy measures of puberty such as timing of the pubertal growth spurt vs Tanner stage), 7 and lack of multiple measures of puberty. 8,13 Furthermore, most studies have not had adequate representation of minority populations to examine race and ethnicity differences in the timing of puberty.…”
mentioning
confidence: 99%
“…Los estudios en varones han tenido resultados controvertidos ya que algunos de ellos no han mostrado relación 20 , otros positiva 21 y algunos incluso negativa 22 . Recientemente Crocker et al, demostró en un grupo de 1.066 niños, un claro dimorfismo sexual en el desarrollo puberal de niños y niñas 6 . En los niños se observó que el mayor porcentaje de grasa se asociaba negativamente con el volumen testicular incluso a similares edades óseas.…”
Section: Discussionunclassified
“…En los niños el inicio puberal está determinado por el aumento del volumen testicular y dado que es un examen más invasivo y que requiere la palpación testicular existe un menor número de estudios que en las niñas. Por otro lado algunos estudios han utilizado diferentes criterios al examen físico puberal masculino ya que algunos estudios utilizan palpación testicular [5][6][7] y otros inspección genital 8 .…”
unclassified
“…In the following models, both prolactin and time period were considered continuous to test the trend over time period. First, a model including prolactin level (continuous), time period (continuous, [1][2][3][4][5], and the prolactin-bytime period interaction was fit. The interaction was not significant (P = .999), and thus it was dropped.…”
Section: Longitudinal Data Analysismentioning
confidence: 99%